Meta-analysis of the Relationship among Job Satisfaction, Quality of Work Life and Organizational Commitment to Turnover Intention - Tongsamsi, Kanyaprin; Tongsamsi, Isara (Ph.D. in Social Sciences Journal, 2026)
The objective of this study is to: 1) explore the characteristics of research studies and perform meta-analysis to identify the standardized indices of the relationships between job satisfaction, quality of life at work, organizational commitment, and turnover intention; and 2) compare the differences in the standardized indices of these relationships based on the characteristics of the research studies. This quantitative research utilized meta-analysis techniques with secondary data from 24 quantitative research articles published during 2014-2023, which were selected following the PRISMA 2020 criteria. The research tools consisted of a research quality assessment form and a research characteristics summary form, both validated for content by three experts, with all items having a content validity index above 0.50. Ethical clearance is obtained from the Human Research Ethics Committee. Data analysis employs Rosenthal and Hedges’ meta-analytic methods using JAMOVI software and the MAJOR Meta-Analysis module. The findings are as follows: 1) Most of the studies were conducted in business organizations, with a total sample of 7,489 participants. The meta-analysis revealed that quality of life at work had a significantly high negative standardized index at the .001 level, organizational commitment had a moderate negative standardized index at the .01 level, and job satisfaction had a low negative standardized index with no statistical significance at the .05 level. 2) The comparison of differences in standardized indices based on research characteristics indicated that the type of organization significantly influenced the index for quality of life at work at the 0.05 level. The results of this study can inform human resource development policies and management strategies to prevent and reduce employees' turnover intentions in both public and private organizations.